(untitled) (LEARNing Landscapes, 2009)
This paper presents the case for considering literacy and learning as possessing a distinct set of intellectual properties that set apart literacy in the context of learning from other sorts of intellectual property that we commonly associate with commercial endeavors. It argues for the value of thinking about intellectual properties as a means of preparing the young both for economic life in the age of information, and for appreciating the importance of protecting the state of learning as a special sphere of intellectual activity and thus intellectual property.The example is given of how students’ own contribution of intellectual properties, as a result of their learning, can add something of value to their communities.